Friderike Klauner (1916–1993). Director of the Picture Gallery and First Director of the Kunsthistorisches Museum Wien. A biographical sketch - Susanne Hehenberger (Journal of Art Historiography, 2023)
50 years ago, a woman headed Austria’s largest art museum for the first time. For eight years, Friderike Klauner managed the affairs of the Kunsthistorisches Museum in Vienna with untiring commitment. She introduced some innovations, but also preserved traditions in order to make the valuable, formerly imperial art collection accessible to the interested public in various forms. This essay attempts a biographical approach to the successful art historian. It explores her career and her professional achievements. It wonders why so little has been published about her so far and finally asks what still remains of Friderike Klauner to this day.